The role of family healthcare in the social development of vulnerable school-aged children groups - Hilda Mazarina Devi; Ronasari Mahaji Putri; Yanti Rosdiana (Healthcare in Low-resource Settings, 2023)
The COVID-19 pandemic has compelled children to embrace remote learning and interact more with their immediate families. However, this increased family interaction may pose a potential risk to children's social development. This study aimed to investigates the relationship between family involvement in healthcare and the social development of children. A cross-sectional correlational design was used, involving reliable questionnaires on family healthcare roles and a school-age child social development questionnaire adapted from the V-SMS (Vineland – Social Maturity Scale). Data were collected from 37 parents of 4th and 5th-grade of elementary school students. The data were analyzed using chi-square tests. The study revealed significant associations between family healthcare roles and children's self-direction ability, decision-making, communication skills, and their abilities to dress, eat, and socialize independently. Negative correlation coefficients for specific variables indicated that family healthcare involvement could potentially hinder school-age children's social development. Further research should consider controlling for various factors affecting family healthcare roles and children's social development. Strengthening the family's role, particularly for those facing challenges in fulfilling various tasks, is crucial. Collaboration programs between nursing and family development, such as "Bina Keluarga Remaja" or Adolescent Family Development in schools, can be beneficial. Additionally, further analysis is needed to understand the impact of family healthcare roles on children's social development during the new-normal era.